Extending the Galician Wordnet Using a Multilingual Bible Through Lexical Alignment and Semantic Annotation - Simões, Alberto (2021)
In this paper we describe the methodology and evaluation of the expansion of Galnet – theGalician wordnet – using a multilingual Bible through lexical alignment and semantic annotation.For this experiment we used the Galician, Portuguese, Spanish, Catalan and English versions ofthe Bible. They were annotated with part-of-speech and WordNet sense using FreeLing. Theresulting synsets were aligned, and new variants for the Galician language were extracted. Aftermanual evaluation the approach presented a 96.8% accuracy.